Odpowiedzi

Najlepsza Odpowiedź!
2009-12-05T07:53:21+01:00
I. 3/4 :3/10-(-1 1/6):7/5=3/4*10/3 - (- 7/6)*5/7 = 30/12 + 5/6 = 30/12 + 10/12 = 40/12= 31/3

II. (√ 2 + 1)²+ (√2 - 1)² = (√2)² + 2*√2*1 + 1² + [(√2)² - 2*√2*1 + 1²] = (√2)² +(√2)² + 2 = √(2)² + 2 = √4 + 2 = 2 + 2 = 4
2009-12-05T11:26:54+01:00
1. 3/4 :3/10-(-1 1/6):7/5 = 3/4 * 10/3 + 7/6 * 5/7 = 5/2-5/6= 15/6 - 5/6 = 10/6 = 1 2/3


2. (pierwiastek z 2+1)do kwadratu +(pierwiastek z 2-1)do kwadratu= (√2+1)² + (√2-1)² = (2+1) + (2-1) = 3+1 =4